Blue Economy Concept in Extension Waste of Fish Baung Into Fish Oil in Sungai Paku Village Kampar Kiri, Kampar Regency, Riau Province - Ilza, Mirna; Ikhsan, Ikhsan; Buchori, Buchori (Program Pascasarjana, Universitas Riau, 2019)
Service to the public entitled